Pretreatment changes in drinking: A test of a tailored treatment approach. (17th February 2023) - Stasiewicz, Paul R.; Bradizza, Clara M.; Lucke, Joseph F.; Zhao, Junru; Dermen, Kurt H.; Linn, Braden K.; Slosman, Kim S.; LaBarre, Charles
Abstract: Background: Pretreatment reductions in drinking are well documented and have been demonstrated to predict posttreatment drinking outcomes. Making use of the predictive value of pretreatment change has great appeal in settings that place a premium on efficient clinical decisions regarding appropriate type and intensity of treatment. Methods: This study investigates whether different types and intensities of treatment are appropriate and beneficial for individuals entering treatment for an alcohol use disorder (AUD; N = 201) who make more vs. less pretreatment change in their drinking during a 2‐month pretreatment period. Based on an algorithm derived from pilot research, we derived two independent pretreatment change arms that we called Substantial Change and Minimal Change. Each arm was a parallel, sequentially randomized design consisting of a treatment group and an active control. The Substantial Change arm compared six sessions of relapse prevention treatment (RPT) with 12 sessions of cognitive behavioral therapy for AUD (CBT) as an active control. Both CBT and RPT occurred over a 12‐week period. The Minimal Change arm compared 12 sessions of an integrated motivational intervention combined with CBT (MI/CBT) with 12 sessions of CBT as an active control. The outcome variables were changes in number of days abstinent (NDA) and number of days heavy drinking (NDH) per week. Results: For the Substantial Change arm, a noninferiority analysis revealed that six sessions of RPT were noninferior to 12 sessions of CBT at each posttreatment assessment for both NDA and NDH. For the Minimal Change arm, a superiority analysis failed to detect that MI/CBT was superior to CBT at any posttreatment assessment for both NDA and NDH. Conclusions: In the substantial change arm, results suggest that offering a less intensive initial treatment, like RPT, may lower costs and conserve clinical resources. In the Minimal Change arm, results indicate the need to continue searching for a treatment or treatment enhancements to improve alcohol outcomes. Abstract : This study investigated whether different types and intensities of treatment are appropriate and beneficial for individuals entering treatment for an alcohol use disorder who make more or less pretreatment change in their drinking. For individuals demonstrating substantial change, Relapse Prevention Treatment was noninferior to Cognitive Behavioral Treatment (CBT). For those demonstrating minimal change, integrated Motivational Interviewing plus CBT (MI/CBT) was not superior to CBT alone. Results have implications for treatment efficiency (substantial pretreatment change) and treatment effectiveness (minimal pretreatment change).